The Pleasures and Pains of Self-Employment: A Panel Data Analysis of Satisfaction with Life, Work, and Leisure - Peter van der Zwan; Jolanda Hessels; Cornelius A. Rietveld (Tinbergen Institute, 2015)
We investigate how a transition from paid employment to self-employment in the labor market influences life satisfaction. Furthermore, we consider the dynamics of work and leisure satisfaction because the balance between work and leisure is an important element of life satisfaction. Fixed-effects regressions using German Socio-Economic Panel data (1984-2012) reveal that switching to self-employment benefits life and work satisfaction. The effects on life satisfaction are weak and temporary, but they are pronounced and relatively persistent for work satisfaction. However, the gain in work satisfaction is outweighed by a decrease in leisure satisfaction, thus placing work-life balance under severe pressure.
Keywords: I31; J24; J28; J31; L26; 330; Self-employment; Entrepreneurship; Life satisfaction; Work satisfaction; Work-life balance